Leviathans : multinational corporations and the new global history - Chandler, Alfred Dupont; Mazlish, Bruce, 1923-2016 (Cambridge, 2005)
Leviathans is a ground-breaking exploration of multinational corporations and differs from other books on the subject by offering the reader a totally global perspective of multinationals. The book paints a compelling and coherent picture of the way these businesses affect almost all areas of our existence.